2022
DOI: 10.2147/idr.s381466
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Sepsis in a Premature Infant Mediated by Breast Milk: Mother-to-Infant Transmission of Group B Streptococcus Detected by Whole-Genome Sequencing

Abstract: Background Late-onset group B Streptococcus (LOGBS) sepsis is a cause of infection and death in infants. Infected breast milk has been considered a source of neonatal GBS infection and invasive infection. However, mother-to-infant transmission of GBS detected by the high-resolution diagnostic method is rarely reported. Methods This study describes a low-weight premature infant who developed late-onset GBS septicemia 21 days after birth. GBS st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…If the levels of inflammatory factors are elevated, the doctor may recommend further tests and treatment to protect the health of the mother and child. Studies have shown that inflammation during pregnancy is closely correlated with preterm birth, but the relationship between GBS infection and preterm birth has not been clear (16).…”
Section: Serum Inflammatory Factors Are Biomarkers Reflectingmentioning
confidence: 99%
“…If the levels of inflammatory factors are elevated, the doctor may recommend further tests and treatment to protect the health of the mother and child. Studies have shown that inflammation during pregnancy is closely correlated with preterm birth, but the relationship between GBS infection and preterm birth has not been clear (16).…”
Section: Serum Inflammatory Factors Are Biomarkers Reflectingmentioning
confidence: 99%
“…Several studies revealed that late-onset sepsis in preterm infant was derived from contaminated breastmilk expression. 19,20 However, there is still limited evidence regarding the role of breast milk's effects on neonatal sepsis. Therefore, this systematic review and meta-analysis aimed to determine the role of breast milk on neonatal sepsis in preterm and low birth weight infants.…”
Section: Introductionmentioning
confidence: 99%